2013
DOI: 10.18637/jss.v055.i06
|View full text |Cite
|
Sign up to set email alerts
|

Performing the Kernel Method of Test Equating with the Packagekequate

Abstract: In standardized testing it is important to equate tests in order to ensure that the test takers, regardless of the test version given, obtain a fair test. Recently, the kernel method of test equating, which is a conjoint framework of test equating, has gained popularity. The kernel method of test equating includes five steps: (1) pre-smoothing, (2) estimation of the score probabilities, (3) continuization, (4) equating, and (5) computing the standard error of equating and the standard error of equating differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 13 publications
0
41
0
1
Order By: Relevance
“…The R (R Development Core Team, ) package kequate (Andersson, Bränberg, & Wiberg, ) was used for the calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The R (R Development Core Team, ) package kequate (Andersson, Bränberg, & Wiberg, ) was used for the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…All the analyses of the simulated data are based on 500 independent replications. Summary statistics for the data sets used are provided in Tables 1 and 2. The R (R Development Core Team, 2013) package kequate (Andersson, Bränberg, & Wiberg, 2013) was used for the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the data was done with SPSS and FACTOR (Lorenzo-Seva & Ferrando, 2006). The equate R package (Albano, 2016) was used for traditional equating methods analyses and the kequate R package (Andersson, Branberg & Wiberg, 2013) was used for kernel equating methods analyses (R Core Team, 2017).…”
Section: Equating Design and Data Analysismentioning
confidence: 99%
“…In the simulation using the symmetric setting, the true score probabilities for the EG design were the fitted score probabilities from chapter 7 of von Davier et al (), and the true score probabilities for the NEAT design were the simeq data found in the kequate package Andersson, Bränberg, & Wiberg, ). In the skewed setting, the true score probabilities were the fitted score probabilities based on score samples created by multiplying beta random numbers (with shape parameters 5 and 2) by the maximum score value.…”
Section: Empirical Studymentioning
confidence: 99%
“…Let the p th moments of scores from X and eX(normalY) be denoted by μp(normalX)=j=1J(xj)prj and μp(eX(Y))=k=1K(eX(yk))psk, then the PRE is defined as PRE (p)=100μp(eX(Y))μp(normalX)μp(normalX)(von Davier et al., ). The evaluation and simulations were performed using R (R Core Team, ) and the kernel equating package kequate (Andersson et al, ).…”
Section: Empirical Studymentioning
confidence: 99%